Valor da Flexibilidade em Decisões de Investimento Sequenciadas: uma Análise Comparativa de Duas Metodologias - da Silva Leitão, Antonio Carlos; Carino Bouzada, Marco Aurélio (Revista ADM.MADE, 2010)
This work intends to compare the Real Options methodology and the Uncertainty Situation Strategic Approach (SILVEIRA, 1993; 2006) in relation to how they deal with the value of flexibility in real assets investments. The methodological proposal is detailed in a comparative exercise with the aid of two case studies, performed by the Real Options approach, by Copeland & Antikarov (2001). Both cases deal with sequential decisions about expansion, abandonment or continuity regarding investment projects. The cases were reinterpreted and represented by political variables and scenarios temporally set, in agreement with Silveira (1993, 2006). The resulting payoffs from each strategy are discounted cashflows, submitted to minimax decision criteria. Through uncertainty modeling, advantages and disadvantages of both methodologies are pointed out, considering the current development stage of the assets market in Brazil, when compared to the markets and institutional environment from where the Real Options methodology was originated. This work ratifies the methodological research relevance regarding the investments flexibility value under higher uncertainty situations.